Preliminary studies on the effect of excretory secretory (ES) Ascaris lumbricoides antigens on colorectal cell line viability - Ab Talib, N.N.; Nisha, M.; Ramasamy, Rajesh; Pang, J.C (Malaysian Society for Parasitology, 2024)
Helminth parasites are a group of complex metazoans from various taxonomic families. Excretory secretory (ES) by-products, secreted by living parasites from the surface, appeared to modulate the host immunological response towards helminth infection. This study aims to investigate the effect of ES antigen from helminth parasite on colorectal cell viability. Worm were cultured in phosphate-buffered saline (PBS x1) at 37°C for 24 hours after being rinsed in sterile PBS. Using a mortar and pestle, the worm was crushed vigorously using PBS. The obtained excretory secretory (ES) antigens were extracted and filtered using a 0.22 µM filter and stored at -20°C for further assay. For LCMS, 100 µl of the extract was analysed using Agilent ZORBAX Eclipse Plus C18 Rapid Resolution HT. The extraction of ES antigen (10 µg/ml and 20 µg/ml) was used for cell viability studies using CRC cell line HCT 116. Cell viability and MTT assay were conducted as per the protocol mentioned in the MTT kit. The liquid chromatography and mass spectrometry (LCMS) data indicated that the ES antigen contained metabolic compounds, namely fatty acid, amino alcohol, indoles, sterols, glycosides, and sphingoids. For the Ascaris lumbricoides LCMS analyses, around 405 metabolic peaks were detected. Out of which, 58 were detected via the database were identified, while several compounds detected have anticancer properties. The MTT assay indicated that after 24 hours and 48 hours of exposure, all treated cells showed a decrease in cell viability compared to the control group. The preliminary studies demonstrated that the ES antigen from Ascaris lumbricoides has some ability to decrease the cell viability of the HCT116 CRC cell line. Further studies are needed to examine the cell cycle arrest and apoptosis effect of the ES antigen towards the CRC cell line.